2021
DOI: 10.3390/pathogens10020099
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design and Preliminary Serological Analysis of a Novel Multi-Epitope Vaccine Candidate Against Onchocerciasis and Related Filarial Diseases

Abstract: Onchocerciasis is a skin and eye disease that exerts a heavy socio-economic burden, particularly in sub-Saharan Africa, a region which harbours greater than 96% of either infected or at-risk populations. The elimination plan for the disease is currently challenged by many factors including amongst others; the potential emergence of resistance to the main chemotherapeutic agent, ivermectin (IVM). Novel tools, including preventative and therapeutic vaccines, could provide additional impetus to the disease elimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 152 publications
2
9
0
Order By: Relevance
“…It is notable that there is a partial overlap between the sequence and position of epitope 3 of Ov-103 discovered here and that of a previous study where peptide arrays were performed using sera from patently O. volvulus infected humans [56]. Furthermore, both epitope 2 and 4 of Ov-103 identified in this study have also been identified as both human B-cell and helper T-cell epitope candidates through computational analysis, again suggesting a commonality between bovine and human responses, as well as a potential expansion of their role and importance to stimulation of adaptive T-cell responses [57]. Due to the small sample size, it was not possible to draw any conclusions on the importance of these epitope-specific responses for parasite killing.…”
Section: Discussionsupporting
confidence: 72%
“…It is notable that there is a partial overlap between the sequence and position of epitope 3 of Ov-103 discovered here and that of a previous study where peptide arrays were performed using sera from patently O. volvulus infected humans [56]. Furthermore, both epitope 2 and 4 of Ov-103 identified in this study have also been identified as both human B-cell and helper T-cell epitope candidates through computational analysis, again suggesting a commonality between bovine and human responses, as well as a potential expansion of their role and importance to stimulation of adaptive T-cell responses [57]. Due to the small sample size, it was not possible to draw any conclusions on the importance of these epitope-specific responses for parasite killing.…”
Section: Discussionsupporting
confidence: 72%
“…A preliminary immunological test with this multi-epitope vaccine candidate revealed its strong reaction to antibodies in sera from putatively immune or infected individuals living in O. volvulus -endemic areas as well as from loiasis individuals, but not with the normal control sera from European individuals. These results support its further evaluation as a vaccine candidate for onchocerciasis ( Shey et al., 2021 ). Immuno-informatics tools and high-density peptide array were used to screen the immunodominant epitopes from the same 8 promising vaccine candidates as mentioned above using sera from onchocerciasis patients and healthy controls.…”
Section: Lead O Volvulus Vaccine Candidatessupporting
confidence: 70%
“…The higher the score, the higher the chance of inducing IFN-g (70). Although the IFN epitope server has limitations regarding the number of residues that can be used for prediction (71), it is a common online prediction server used for vaccine design (70,(72)(73)(74). Therefore, the epitopes with positive results for the IFN-g response were selected for further prediction.…”
Section: Antigenicity Toxicity Allergenicity Of Selected Epitopesmentioning
confidence: 99%